PENGARUH SENAM LANSIA TERHADAP TEKANAN DARAH DI PANTI SOSIAL TRESNA WERDHA BUDI LUHUR JAMBI - M. Dody Izhar (Universitas Batanghari Jambi, 2017)
Hypertension is commonly found in the elderly. This is because increasing age, the body's cells decline in function. One of the factors that can reduce hypertension are elderly gymnastics. This research is a kind of quasi experimental design with one group pre test and post-test design. The population of elderly who suffer from hypertension in Social Institutions Tresna Werdha Budi Luhur city of Jambi at least 21 people, the sampling method using purposive sampling with a sample of 10 people. Overall analysis using statistical analysis software to test significance level of p<0.05. The results showed no decrease in average systolic blood pressure in the elderly (8.112 mmHg ± 5.930 mm Hg) and diastolic blood pressure (3.824 mmHg ± 2.949 mmHg). Based paired dependent sample t-test, is known to have the effect of significantly decreased systolic blood pressure (t=4.235, p=0.002) and blood pressure diastolic ((t=4.100, p=0.003). This means that there is the influence of gymnastics elderly against blood pressure in the elderly with hypertension in Social Institutions Tresna Werdha Budi Luhur city of Jambi. the study concluded that older exercisers can lower blood pressure in hypertensive patients.Keywords: Gymnastics, blood pressure, elderly